Persepsi Petani Padi dalam Memanfaatkan Layanan Kredit Usaha Rakyat (KUR) BRI di Kota Metro, Provinsi Lampung - Syafani, Tyas Sekartiara; Ibnu, Muhammad; Gitosaputro, Sumaryo; Soepraktikno, Serly Silviyanti (Fakultas Pertanian, Universitas Lampung, 2025)
The People's Business Credit Program (KUR) is the government's effort to increase access to sources of financing for farming and entrepreneurship development. This study aims to analyze rice farmers' perceptions of KUR services and the factors that influence rice farmers' decisions in utilizing KUR. This research was conducted using a survey method in May-October 2022 in Metro City. The number of samples was 35 rice farmers, consisting of 10 KUR recipient farmers and 25 non-KUR farmers. The sampling technique used is snowball sampling. The data collection technique used in-depth interviews and were analyzed descriptive quantitatively. The results showed that rice farmers' perceptions of KUR in Metro City based on the five dimensions of service quality were satisfied. The KUR program is very helpful for the sustainability of rice farming in Metro City. Factors that influence rice farmers' decisions in utilizing KUR were the number of household working members, side jobs, level of knowledge about KUR, and experience in making KUR loans. To increase farmers' knowledge of KUR, massive socialization is needed regarding the benefits of the KUR program. The formation of the 'entrepreneur' character also needs to be a priority to encourage farmers to have businesses or be more/business oriented. Keywords: capital, KUR, perception, service